The role of the theory of nursing in improving the quality of nursing care - Glińska, Jolanta; Brzezińska, Edyta; Lewandowska, Małgorzata; Borowiak, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Today, the intention is to provide the better quality of care, not only in the disease but also in health. Knowledge of the theory of nursing enables nurses the perception of full reality of their profession, and hence is the foundation to provide excellent quality of nursing care. Objective. Evaluate the possibility of turning the theory of nursing into practice and its impact on quality of care in the opinion of students and nurses. Material and methods. The analysis covered 200 respondents (100 nursing students and 100 nurses). The study was conducted using a diagnostic survey. Research technique was a custom questionnaire survey. Correlation analysis was performed by a factor of Pearson's R, Spearman's RHO, and the Student T test for independent samples. Results. The analysis of the overall data shows that the majority of students (68%) and nurses (78%) considered the introduction of the theory of nursing, as a model, which increases the quality of nursing care. In the group of students the largest number of people were in favor of models D. Orem ( 38%), F. Nightingale (29%) and the model of V. Henderson (18%). Similarly was shaped the opinion of nurses. Conclusions. According to the studied two groups, theories of nursing have a positive impact on the quality of nursing care. Significant importance have theories F. Nightingale, V. Henderson and D. Orem.